Penerapan Metode Transportasi untuk Mengoptimalkan Waktu Pengiriman Produk pada PT. Sera Banyu Urip - Nurhayana, Cepi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to find out and analyze the optimal delivery time, to find out and analyze the initial solution for transportation costs using the North West Corner, Least Cost, and Vogel's Approximation Method (VAM) methods for the initial solution, to find out and analyze the optimization of shipping costs goods using Stepping Stone and Modified Distribution at PT. Sera Banyu Urip Ciputat, South Tangerang. To achieve this research, researchers used qualitative methods by conducting documentation, observation, interviews and triangulation using a research instrument in the form of the PDCA method. For the study population at PT. Sera Banyu Urip, South Tangerang. The results showed that after using the transportation method there was a very significant increase in the delivery of each vehicle which experienced an increase in delivery, and costs became more efficient.